Biochemical markers of pathology in rat kidneys after “Mild” stress - Pavlenko, K. (Journal of Education, Health and Sport, 2025)
Background. It is known that stress negatively affects the condition of the kidneys, activating oxidative stress in them. Aim. To investigate the effect of “mild” stress on biochemical markers of pathology, such as the level of proteolysis, the state of the kallikrein-kinin system, and the rate of oxidation processes. Methods. "Mild" stress was induced in rats by exposure to −20 °C for 5 minutes. 5 and 24 hours after stress, the rate of casein hydrolysis (pH 7,6) was determined in kidney homogenates by the Kunitz method, the activity of BAEE esterase by the spectrophotometric method, and the rate of ascorbic acid oxidation. Results. Stress causes a significant decrease in proteolysis activity after 24 hours and a significant increase in the rate of ascorbic acid oxidation after just 5 hours. Conclusion. “Mild” stress reduces the level of proteolysis, but significantly increases the level of oxidation, which can be considered a protective reaction.